2021
DOI: 10.1038/s41598-021-89526-4
|View full text |Cite
|
Sign up to set email alerts
|

Interacting with virtual objects via embodied avatar hands reduces pain intensity and diverts attention

Abstract: The current study introduces a new paradigm for exploring cognitive factors in pain. Interacting with virtual objects via embodied avatar hands increased the illusion of “being there” in the virtual world, increased VR analgesia for acute pain, and reduced accuracy on an attention demanding task. Twenty-four healthy volunteer college students participated in this within-subject randomized crossover design study. During Phase 1, each participant received brief thermal pain stimuli during interactive embodied av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…These theories purport that pain is influenced by sensory, affective, and cognitive inputs (Basil, 1994;Indovina et al, 2018;Smith et al, 2020). Since the human brain has a finite processing capacity, VR saturates the brain with engaging positive stimuli thus blocking/distracting from the pain signals resulting in pain reduction (Kahneman, 1973;Eccleston, 1999Eccleston, , 2001Hoffman et al, 2007Hoffman et al, , 2011Tack, 2019;Hoffman, 2021). We posit that the success of VR in our setting was likely the result of several factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories purport that pain is influenced by sensory, affective, and cognitive inputs (Basil, 1994;Indovina et al, 2018;Smith et al, 2020). Since the human brain has a finite processing capacity, VR saturates the brain with engaging positive stimuli thus blocking/distracting from the pain signals resulting in pain reduction (Kahneman, 1973;Eccleston, 1999Eccleston, , 2001Hoffman et al, 2007Hoffman et al, , 2011Tack, 2019;Hoffman, 2021). We posit that the success of VR in our setting was likely the result of several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hardware and software play an important role in the effectiveness of VR related to level of immersion and presence, which may be affected by the degrees of freedom, field of view, interactivity, sound quality, frame rate, and other characteristics (Hoffman et al, 2006;Hoffman, 2021). In our assessment, we utilized two similar 6DoF HMDs, one tethered and one standalone, due to Bluetooth connectivity issues within the facility, but found no statistically significant difference between the two in regard to impact on pain or anxiety.…”
Section: Hardware and Softwarementioning
confidence: 99%
“…Emerging evidence is pointing towards continued rapid evolution of increasingly more immersive but affordable VR systems that will be able to further amplify the potency of adjunctive VR distraction for acute pain, and VR therapy for persistent pain (Al-Ghamdi et al, 2020;Wender et al, 2009;Hoffman et al, 2006;Hoffman, 2021;Keefe et al, 2012). Acute pain laboratory studies have helped isolate factors that increase analgesic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Goggles that stimulate peripheral vision are more effective at reducing pain than narrower field of view goggles (Hoffman et al, 2006b), and interactive worlds such as SnowWorld (see Figure 1) are more effective than passive versions of the same worlds (Wender et al, 2009). Several recent studies have shown that immersive add-ons such as interactive eye tracking (Al Ghamdi et al, 2020); and interactive avatar cyber-hands (see Figure 2) (Hoffman, 2021), significantly increase VR analgesia for acute pain. Unlike opioidbased analgesia, carefully designed adjunctive VR pain distraction treatments customized for patients (e.g., designed to minimize simulator sickness) had little or no side effects, even with more immersive VR systems, i.e., higher (more immersive, more effective) doses of VR distraction.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, XR is expanding in many areas of human activity from games, movies/theaters/museums, travels, businesses, through senses, whether they provide additional information about the real world or create completely unreal, simulated worlds that we can experience. Currently, XR is expanding in many areas of human activity from games, movies/theaters/museums, travels, businesses, through the military, professional sports and education, to (neuro)science, healthcare and modern medical practice, and much more [17][18][19][20][21][22][23][24].…”
Section: Introduction 1novel Information Technologies and Virtual Reality Environmentsmentioning
confidence: 99%